Myelofibrosis in a Child with Tuberculosis: A Case Report - Malla, K; Malla, T; Thaplial, A (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Myelofibrosis (MF), or fibrosis of the bone marrow, is an uncommon condition in children. Fewer than 100 cases have been described in the medical literature. Most cases in children arise secondary to other disease processes. We present a case of Myelofibrosis in a 12-year-old girl. The purpose of reporting this case is that this child had a diagnostic dilemma and was sent home with poor prognosis but with proper diagnosis and treatment she improved and may have a complete cure, as the myelofibrosis was secondary to tuberculosis. Key words: myelofibrosis, tuberculosis, acute megakaryoblastic leukemia (AMKL) doi:10.3126/jnps.v27i2.1588 J. Nepal Paediatr. Soc. Vol.27(2) p.90-92